2020
DOI: 10.1007/s00167-020-06234-8
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral ACL tears strongly contribute to high rates of secondary ACL injuries in professional ski racers

Abstract: Purpose To analyse the efects of graft selection, sex, injury complexity and time to return to competition on the odds to sufer secondary ACL injury (either re-rupture or contralateral ACL tear) in professional alpine skiers. Methods The database of a specialised joint surgery clinic was screened for professional alpine skiers who had participated in competitions at the FIS race, European Cup and World Cup level prior to having to undergo a primary ACL reconstruction, and who had returned to the same competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The main findings of this study included the observations that elite alpine skiers who underwent ACLR + LEAP had a significantly lower risk of graft rupture as compared with those who underwent an isolated ACLR (HR, 5.286 [95% CI, 1.068-26.149]; P = .0412) and that those who had combined procedures experienced a low rate of ACL graft rupture (6.5%, with a mean exposure time of 2.5 years). This rate can be considered remarkably low given that elite alpine skiing is a notoriously high–risk sport for second ACL injury, as reported in the literature 2,4,23,24,36 and in the current study, with 34.0% of the isolated ACLR group experiencing graft rupture and 37.3% of the overall study population experiencing contralateral ruptures. Although this is the first comparative study of ACLR + LEAP vs isolated ACLR in professional athletes, the results are consistent with those of recent systematic reviews and numerous contemporary comparative studies demonstrating either a downward–trending or significantly reduced graft rupture rate with combined procedures when compared with isolated ACLR in high–risk populations, such as young patients participating in pivoting sports, those with hyperlaxity or chronic ACL injury, and those undergoing revision ACLR.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…The main findings of this study included the observations that elite alpine skiers who underwent ACLR + LEAP had a significantly lower risk of graft rupture as compared with those who underwent an isolated ACLR (HR, 5.286 [95% CI, 1.068-26.149]; P = .0412) and that those who had combined procedures experienced a low rate of ACL graft rupture (6.5%, with a mean exposure time of 2.5 years). This rate can be considered remarkably low given that elite alpine skiing is a notoriously high–risk sport for second ACL injury, as reported in the literature 2,4,23,24,36 and in the current study, with 34.0% of the isolated ACLR group experiencing graft rupture and 37.3% of the overall study population experiencing contralateral ruptures. Although this is the first comparative study of ACLR + LEAP vs isolated ACLR in professional athletes, the results are consistent with those of recent systematic reviews and numerous contemporary comparative studies demonstrating either a downward–trending or significantly reduced graft rupture rate with combined procedures when compared with isolated ACLR in high–risk populations, such as young patients participating in pivoting sports, those with hyperlaxity or chronic ACL injury, and those undergoing revision ACLR.…”
Section: Discussionmentioning
confidence: 48%
“…Return to international competition was defined by the first date on which skiers participated in competitions at the FIS race, European Cup, or World Cup after ACLR. The interval between surgery and return to international competition was calculated and categorized according to Csapo et al 4 into early returners (<10 months) and late returners (≥10 months).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found similar results on professional ski racers with an increased risk of contralateral ACL injury in athletes who had an isolated ACL injury. 39 Importantly, when these two factors (non-contact and isolated ACL injury) were combined, we found that as many as 42% of players sustained a second ACL injury. The increased second ACL injury risk of non-contact and isolated ACL injuries is a novel and clinically very relevant finding which needs to be incorporated in the counselling of the player at the time of the index ACL injury in parallel with appropriate risk stratification management (such as appropriate communication of the second ACL injury risk before and following ACLR based on injury mechanism and pattern).…”
Section: Risk Factors For Second Acl Injurymentioning
confidence: 76%
“…Due to its extremely high ACL injury risk, skiing has had the most ACL IPP research of individual sports. [119][120][121] However, sports such as gymnastics 122 and wrestling 122,123 also carry high risk for ACL injury and require further prevention work due to their unique demands. There is a sparsity of injury surveillance data on smaller "extreme" sports such as skateboarding, BMX, break dancing, or parkour.…”
Section: Future Directionsmentioning
confidence: 99%